Solubility of acetaminophen in polyethylene glycol 400 + water mixtures according to the extended hildebrand solubility approach (2012)
The Extended Hildebrand Solubility Approach(EHSA) was applied in the presentwork to evaluate the solubility of theanalgesic drug acetaminophen (paracetamol)in polyethylene glycol 400 + watermixtures at 298.15 K. An acceptablecorrelative capacity of EHSA was foundusing a regular polynomial model in orderfour (overall deviation below 0.7%),when the W interaction parameter is relatedto the solubility parameter of themixtures. Thus, the deviations obtainedin the estimated solubility with respect toexperimental solubility were lower thanthose obtained directly by means of anempiric regression of the experimentalsolubility as a function of the mixtures’solubility parameters (close to 1.5%).